2016
DOI: 10.1532/hsf.1328
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Pericardial Fluid and Pericardial Biopsy: Single Center Experiences

Abstract: Recurrent pericardial effusion/pericardial tamponade are entities frequently diagnosed, and surgical interventions may be needed either for diagnosis and/or treatment, but specific etiology can rarely be obtained in spite of pathological examination of either pericardial tissue or fluid. For increasing the probability of a specific diagnosis both the pericardial fluid and the pericardial tissues have to be sent for pathologic examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The patient was discharged with symptomatic treatment, but she was readmitted 1 month later with malaise, chest pain with hypothermia, and echocardiography indicated a small pericardial effusion. A single-center study involving 174 patients suggested that pericardial tissue biopsy is feasible for recurrent pericardial effusions to improve the likelihood of diagnosis in patients ( 17 ). Ultimately, this patient was diagnosed with TBP when a pericardial biopsy was performed to identify the source of the pericardial effusion, and a granuloma was found.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was discharged with symptomatic treatment, but she was readmitted 1 month later with malaise, chest pain with hypothermia, and echocardiography indicated a small pericardial effusion. A single-center study involving 174 patients suggested that pericardial tissue biopsy is feasible for recurrent pericardial effusions to improve the likelihood of diagnosis in patients ( 17 ). Ultimately, this patient was diagnosed with TBP when a pericardial biopsy was performed to identify the source of the pericardial effusion, and a granuloma was found.…”
Section: Discussionmentioning
confidence: 99%